(untitled) (Global Journal of Management and Business Research, 2018)
Corporate Social Responsibility CSR thought did not provide any distinct and precise definition of social responsibility in the area of workers rights As well as this thought did not specify any characteristics of the activities transactions measures and procedures established and adopted by the corporations to fulfill their commitment to the workers As a result of this shortcoming there is no any accurate classification of these activities transactions measures and procedures that can contribute to understanding the dimensions of social responsibility in this area correctly Therefore as is well known the intellectual inadequacy of any theory results in a confused understanding of the meaning of that theory In fact this is what the CSR thought is still suffering As a result it will be certain the occurrence of misunderstandings and wrong practices disclosing the corporate social performance in the field of human resources about CSR in the area of workers rights In this study all activities transactions measures and procedures in force and expected to be followed by corporations to fulfill their commitment towards the rights of their workers were identified and classified in homogeneous groups characterized by specific characteristics and common purposes This study will contribute to achieving a deep understanding of all parties interested in this subject as well as a comprehensive disclosure quantitative and descriptive of social performance in this area in a more accurate and comprehensive manner